A generic model for analyzing nexus issues of households bioenergy use - Utkur Djanibekov; Robert Finger; Dawit Diriba Guta; Varun Gaur; Alisher Mirzabaev (University of Bonn, Center for Development Research (ZEF), 2016)
Bioenergy is a major source of energy in developing countries. However, increasing demand for agricultural commodities can lead to a stronger competition for natural resources with the bioenergy production. The nexus among energy, food production and natural resource use may result in trade-offs and synergies. Accordingly, it is important to consider multidimensional aspects of bioenergy, assess the potential for bioenergy options for meeting rural households demand for energy, while increasing their incomes, enhancing food security and reducing potential negative effects. For addressing these interrelated issues within a single framework, we develop a generic household model that allows analyzing the ex-ante potential impacts of bioenergy use on rural households in developing countries. The model relies on dynamic programming approach and is able to evaluate the impacts of bioenergy on livelihoods of households, on environment, and on natural resource use over time. The model explicitly considers decision making among various members of household, including men, women and children. We also trace direct and spillover impacts of policy and technological changes among different socio-economic categories of households.
Keywords: C61; D63; O13; O33; Q4; Q12; 330; dynamic programming; equity; gender; technological innovations; environment; trade-offs; spillovers; synergies